2020
DOI: 10.1055/s-0040-1709994
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Analog AVR-25 Prevents Experimental Bronchopulmonary Dysplasia

Abstract: Infants born extremely preterm are at a high risk of developing bronchopulmonary dysplasia (BPD) which is characterized by large, simplified alveoli, increased inflammation, disrupted and dysregulated vasculogenesis, decreased cell proliferation, and increased cell death in the lungs. Due to lack of specific drug treatments to combat this condition, BPD and its long-term complications have taken a significant toll of healthcare resources. AVR-25, a novel immune modulator experimental compound, was able to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, if prevented early, this condition can be mitigated to improve the respiratory status and developmental delays in childhood of these preterm infants. We have recently reported that AVR-48 decreases severe lung inflammation in LPS-, hyperoxiaand CLP-induced ARDS in adult mice while AVR-25, another close analog of AVR-48, can prevent lung injury in the neonatal mouse model of experimental BPD [19]. In order to facilitate bulk manufacturing, and improve physicochemical properties, we have optimized the chemical series and identified AVR-48 as a better lead than our previously reported compound, AVR-25.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, if prevented early, this condition can be mitigated to improve the respiratory status and developmental delays in childhood of these preterm infants. We have recently reported that AVR-48 decreases severe lung inflammation in LPS-, hyperoxiaand CLP-induced ARDS in adult mice while AVR-25, another close analog of AVR-48, can prevent lung injury in the neonatal mouse model of experimental BPD [19]. In order to facilitate bulk manufacturing, and improve physicochemical properties, we have optimized the chemical series and identified AVR-48 as a better lead than our previously reported compound, AVR-25.…”
Section: Discussionmentioning
confidence: 99%
“…After assessment of the safety profile of the AVR-48, and confirmation of t dose to be used, we next performed experiments to evaluate the therapeutic effec lungs in our experimental BPD mouse model, as previously described [19,[23][24][25] characterized by enlarged simplified alveoli with large air sacs, a thickened septu thin alveolar epithelium (Figure 2A), accompanied by an overall decrease in alve proliferation, decreased or dysregulated angiogenesis, and increased cell death. A features were restored after injection of two doses of AVR-48, IP (10 mg/kg) on and P4.…”
Section: Avr-48 Restored Lung Morphology and Improved Alveolar Cellular Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, inhibition of chitotriosidase and acidic mammalian chitinase is regarded as a drug target for respiratory diseases [ 82 ]. However, it has been shown that a chitin analog AVR-25 partially alleviated pulmonary dysregulation in a hyperoxia-induced experimental mouse model of bronchopulmonary dysplasia by suppressing inflammation [ 83 ]. These findings indicate that chitin may have both beneficial and detrimental effects.…”
Section: Potential Applications Of Chitin and Chitosan Oligosacchamentioning
confidence: 99%